The role of cross-cultural communications in the activities of socio-cultural managers - Низола , Марія Олександрівна (Інформаційні технології і системи в документознавчій сфері, 2024)
This article explores the role of cross-cultural communication in the activities of socio-cultural managers. It emphasizes the importance of understanding cultural differences for effective cooperation in the international environment and promotion of national cultural products. The article also highlights the need for developing cross-cultural competence for socio-cultural managers, which includes the ability to communicate effectively and understand individuals from different cultures. The authors stress that successful work in this field depends on the development of cultural sensitivity, tolerance, and leadershi.